Research on strategy of green electricity acquisition transaction of park-level energy internet by using STP - Zheng, Zhe; Tian, Hui; Zhu, Ping; Chi, Yingying; Liu, Yong; Jia, Xiaoguang (Frontiers in Energy Research, 2022)
In order to save resources and reduce air pollution, human beings have begun to pay attention to the production and use of photovoltaic, wind power and other green power. Due to the difficulty of direct transaction between green power producers and power users, a park-level energy Internet has been proposed and used to connect all kinds of green electricity with power users. Then park users can effectively buy and use green electricity. Taking the park-level energy Internet as the scenario, this paper constructs a transaction model between green power operators and green power producers. The model is a dynamic game of complete and perfect information. The dynamic characteristics of this game model are analyzed by using semi-tensor product method, and corresponding strategies are provided for all players. From the results obtained, it is easy to find that in many cases, the strategy profile of all participants are constantly changing to obtain more profits, rather than stable at some traditional Nash equilibrium.